2006
DOI: 10.1128/jb.00608-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adhesion Threads of Deinococcus geothermalis as Type IV Pili

Abstract: Deinococcus geothermalis E50051 forms tenuous biofilms on paper machine surfaces. Field emission electron microscopy analysis revealed peritrichous appendages which mediated cell-to-surface and cell-to-cell interactions but were absent in planktonically grown cells. The major protein component of the extracellular extract of D. geothermalis had an N-terminal sequence similar to the fimbrial protein pilin annotated in the D. geothermalis DSM 11300 draft sequence. It also showed similarity to the type IV pilin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation. Since then, similar findings have been reported for a number of bacteria and archaea, including (but not limited to) V. cholerae, A. actinomycetemcomitans, Aeromonas caviae, Shewanella oneidensis, Legionella pneumophila, Caulobacter crescentus, Deinococcus geothermalis, C. perfringens, and Sulfolobus acidocaldarius (40,44,102,133,178,342,389,398,408,431).…”
Section: Biofilm Formation and Remodelingsupporting
confidence: 49%
“…O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation. Since then, similar findings have been reported for a number of bacteria and archaea, including (but not limited to) V. cholerae, A. actinomycetemcomitans, Aeromonas caviae, Shewanella oneidensis, Legionella pneumophila, Caulobacter crescentus, Deinococcus geothermalis, C. perfringens, and Sulfolobus acidocaldarius (40,44,102,133,178,342,389,398,408,431).…”
Section: Biofilm Formation and Remodelingsupporting
confidence: 49%
“…We hypothesize that PilO has evolved to prevent the transfer of long O polysaccharides that would likely impede pilin transport and pilus assembly. On the con- In addition to Pseudomonas and Neisseria, pilin glycosylation has been described recently for Deinococcus geothermalis (33) and it has been proposed that pilin is also glycosylated in Francisella tularensis (15). Although more experiments are required to confirm the presence of glycans attached to F. tularensis pilin, an ORF homologous to PilO has been identified in its genome, suggesting that the glycosylation process may occur by the same pathway described here.…”
Section: Discussionmentioning
confidence: 88%
“…The amyloid coat on the merozoite surface was described as patches of regular denticulation in early schizogony and later formed long bristles and filaments that appeared thicker at apices than their stems and thus suggested the presence of a complex formation (42). Interestingly, similar filamentous extracellularly extended structures have also been reported in many eukaryotic and prokaryotic cells termed adhesins, extracellular appendages, fibrils, and filaments (43)(44)(45)(46). However, the components of merozoite's amyloid coat have remained unexplored so far.…”
Section: Discussionmentioning
confidence: 90%